Decreased peak expiratory flow in pediatric passive smokers - Fitri Yanti; Muhammad Ali; Ridwan M. Daulay; Wisman Dalimunthe; Rini Savitri Daulay (Paediatrica Indonesiana, 2011)
Background Indonesia ranks fifth among countries with the highest aggregate levels of tobacco consumption in the world. Infants and children exposed to environmental tobacco smoke have increased rates of asthma, respiratory and ear infections, as well as reduced lung function. The effects of tobacco smoke exposure on lung function in children have been reported to be dependent on the source of smoke and the length and dose of exposure. Lung function may also be affected by a child’s gender and asthma status.Objective To compare peak expiratory flow (PEF) in pediatric passive smokers to that of children not exposed to second hand smoke, and to define factors that may affect PEF in passive smokers.Methods In August 2009 we conducted a cross-sectional study at an elementary school in the Langkat district. Subjects were aged 6 to 12 years, and divided into two groups: passive smokers and those not exposed to secondhand smoke. Subjects’ PEFs were measured with a Mini-Wright peak flow meter. Measurements were performed in triplicate with the highest value recorded as the PEF. Demographic data including age, sex, weight, height, family income, parental education levels and occupations were obtained through questionnaires.Results Of the 170 participants, 100 were passive smokers and 70 were not exposed to secondhand smoke. Age distribution, weight and height were similar in both groups. We observed a significant difference in PEFs between the group of passive smokers and the group not exposed to secondhand smoke, 211.3 L/minute (SD 61.08) and 242.7 L/minute (SD 77.09), respectively (P < 0.005). The number of years of exposure to smoke (P = 0.079) and the number of cigarettes smoked daily in the household (P = 0.098) did not significantly influence PEF.Conclusion The PEF in pediatric passive smokers was significantly lower than that of children not exposed to secondhand smoke. PEF in passive smokers was not influenced by the number of years of smoke exposure or the number of cigarettes smoked daily in the household.